Package ‘regnet’ - Ren, Jie; Jung, Luann C.; Du, Yinhao; Wu, Cen; Jiang, Yu; Liu, Junhao (My University, 2022)
Network-based regularization has achieved success in variable selection for high-dimensional biological data due to its ability to incorporate correlations among genomic features. This package provides procedures of network-based variable selection for generalized linear models (Ren et al. (2017) <doi:10.1186/s12863-017-0495-5> and Ren et al.(2019) <doi:10.1002/gepi.22194>). Continuous, binary, and survival response are supported. Robust network-based methods are available for continuous and survival responses.
Network-Based Regularization for Generalized Linear Models